Tip Tap Tones: Mobile Microtraining of Mandarin Sounds - Edge, Darren; Cheng, Kai-Yin; Whitney, Michael; Qian, Yao; Yan, Zhijie; Soong, Frank (MobileHCI 2012 Conference on Human Computer Interaction with Mobile Devices and Services, 2012)
Learning a second language is hard, especially when the learner’s brain must be retrained to identify sounds not present in his or her native language. It also requires regular practice, but many learners struggle to find the time and motivation. Our solution is to break down the challenge of mastering a foreign sound system into minute-long episodes of “microtraining” delivered through mobile gaming. We present the example of Tip Tap Tones – a mobile game with the purpose of helping learners acquire the tonal sound system of Mandarin Chinese. In a 3-week, 12-user study of this system, we found that an average of 71 minutes’ gameplay significantly improved tone identification by around 25%, regardless of whether the underlying sounds had been used to train tone perception. Overall, results suggest that mobile microtraining is an efficient, effective, and enjoyable way to master the sounds of Mandarin Chinese, with applications to other languages and domains.
Honorable Mention Award